Positive and Negative Post Performance-Related Thoughts Predict Daily Cortisol Output in University Music Students - Haccoun, Yoav E. Y.; Hildebrandt, Horst; Klumb, Petra L.; Nater, Urs M.; Gomez, Patrick (Frontiers in Psychology, 2020)
Psychophysiological research on music performance has focused on musicians’ short-term affective, cognitive and physiological responses. Much less attention has been devoted to the investigation of musicians’ psychophysiological activity beyond the performance situation. Musicians report having both positive and negative performance-related thoughts (e.g., “My concert was good”, “I made a lot of mistakes”) for days following performances. The potential physiological implications of this post-performance cognitive processing are largely unknown. Salivary cortisol (sC) and salivary alpha-amylase (sAA) are markers of the activity of the hypothalamic-pituitary-adrenal (HPA) axis and the sympathoadrenal medullary system, respectively. The goal of the present study was to investigate whether self-reported positive and negative post performance-related thoughts predict the daily sC output and the daily sAA activity at the between- and within-person levels during a two-day period following a solo music performance. Seventy-two university music students collected saliva samples six times per day and reported their positive and negative performance-related thoughts for two days after a solo performance. We tested between-person and within-person components of positive and negative post performance-related thoughts as predictors of the diurnal area under the curve with respect to ground (AUCg) for sC and sAA while adjusting for relevant person-level and day-level variables. Negative post performance-related thoughts were positively associated with sC AUCg both at the between- and within-person levels, whereas positive post performance-related thoughts were negatively associated with sC AUCg at the between-person level. Post performance-related thoughts did not significantly predict sAA AUCg. These findings provide evidence for a relationship between affectively valenced cognitive processing of a recent music performance and the activity of the HPA axis. Although the directionality of this relationship remains to be established more conclusively, the study makes a significant contribution to the literature on the prolonged psychophysiological effects of music performance situations and more broadly of social-evaluative stressors. Integrating the topic of post-performance cognitive processing and its optimal management into performance training programs would likely have positive effects on music students.